A systematic approach for robust repetitive controller design. (September 2016) - Flores, Jeferson V.; Pereira, Luis Fernando A.; Bonan, Guilherme; Coutinho, Daniel F.; Gomes da Silva, João Manoel
Abstract: In this paper, a methodology for the synthesis of repetitive controllers to ensure periodic reference tracking and harmonic disturbance rejection is cast in a robust control framework. Specifically, the Lyapunov–Krasovskii theory is applied to derive LMI-based conditions for designing a state feedback control law with guaranteed stability and performance properties for system parameter variations. Practical experiments in commercial uninterruptible power supplies – UPS are considered to illustrate and discuss some practical implementation aspects of the proposed method. Abstract : Highlights: A detailed analysis to illustrate the impact of the repetitive structure. Systematic design procedure by solving a convex optimization problem. Focus on the application aspects of the proposed method. Experimental results in a commercial 4.3 kVA PWM single phase DC–AC inverter. Results analyzed under performance criteria defined by the IEC 62040-3 standard.